Morphometric Analysis and Host Range of the Genus Pentalonia Coquerel (Hemiptera: Aphididae) Infesting Banana in Java - Willing Bagariang; Purnama Hidayat; Sri Hendrastuti Hidayat (Universitas Gadjah Mada, 2019)
Banana aphid, Pentalonia nigronervosa Coquerel (Hemiptera: Aphididae) is known as vector of Banana bunchy top virus (BBTV) that threatening production of banana worldwide. It was reported recently that P. nigronervosa and P. caladii is “cryptic species”. A good and proper identification is necessary to verify the correct species and its status. Research was conducted to identify and to find the host range of banana aphids in Java. Aphid collection was conducted in several locations in West Java, Central Java, and East Java. Eleven morphometric characters were analyzed to assess the morphometric variations among banana aphids. Morphological identification and principle component analysis (PCA) approach were conducted for accurate identification of banana aphids. Two species of aphids were found during the survey in Java, i.e. P. nigronervosa and P. caladii. P. nigronervosa mostly infested bananas (Musa spp.), and a few was found on heliconia (Heliconia sp.) and banana traveler (Ravenala madagascariensis). In contrast, P. caladii generally infested taro (Colocasia esculenta), turmeric (Curcuma longa), costus (Costus sp.), dumbcane (Dieffenbachia sp.), but rarely on bananas.